Strategic Financial Disclosure: Evidence from Labor Negotiations - WATERHOUSE, JOHN; GIBBINS, MICHAEL; RICHARDSON, ALAN J. (Contemporary Accounting Research, 1993)
Evidence of strategic behavior in public financial disclosure is provided by analyzing 673 disclosures that were made before, during, and after four Canadian labor strikes. Financial disclosures included quantitative and qualitative information about the sampled companies that appeared in print media during the periods of interest. Strategic behavior involved the naming of one actor by another in the disclosures. The analyses showed that disclosure frequency was much higher during and immediately preceding the strikes than in other periods. Network‐analytic techniques were employed to examine the linkages among seven groups of actors that were named in the disclosures. The disclosure networks increased in density during the strikes but became less centralized. Our analysis supports the view that strategic interactions in disclosures are multilateral and dynamic. Thus, any attempt to model financial disclosure during labor negotiations as a bilateral single‐period game would appear to be simplistic. Disclosure management in this setting seems to occur within a complex economic and social setting.